THE USE OF “OPPOSITE” GAME IN IMPROVING STUDENTS VOCABULARIES: CASE OF EIGHTH GRADE STUDENTS OF SMP 9 SEMARANG - Ragil Adhi Praditya (ETERNAL (English Teaching Journal), 2014)
This Final project is discussing about the use of “Opposite” game in improving students’ vocabulary. The objectives of this final project are to find out the implementation of “Opposite” game to improve the students’ vocabulary, the students’ advantages and difficulties using “Opposite” game to improve their vocabulary and some possible solution for the difficulties. This final project is categorized as descriptive qualitative. the data took by doing the observation and collecting the students’ oppinion to describe the implementation of “Opposite” game to improve the students’ vocabulary, know the students’ difficulties and advantages of improving students’ vocabularies through ”Opposite”game. The data analyzed by transcribing the observation and questionnaire into written form. There are the results of analysis of the observation and questionaire. First, the teacher ways in using “Opposite” game in improving students’ vocabulary is good. Second, the students’ facing difficulties in making some clues and guessing some clues in using “Opposite” game in order to improve students’ vocabularies. Third The advantages of using “Opposite” game are the students can memorize vocabulary in an interesting way and improve their speaking and listehning skill in the same time, the teacher can increase students’ motivation and interest by using “Opposite” games.